Perceived international cooperation barriers and the relationship quality – empirical study on Polish SMEs cooperating with partners from China and Germany - Danik, Lidia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
International business scholars still do not pay much attention to international cooperation barriers and their consequences. Although the problem of cooperation barriers is being discussed in the cooperation, open innovation and international cooperation studies, an indepth analyses of barriers which influence the cooperation are missing. This study is devoted to the differences in the Polish companies’ perception of the barriers hampering the establishing of cooperation with German and Chinese partners, and to the influence exerted by the perceived barriers on the indicators of cooperation quality. The analysis was conducted on a sample of 278 Polish exporters and importers cooperating with partners from China and Germany. It was reported that Polish companies observe greater barriers that hamper establishing cooperation with Chinese rather than German partners, and that the perceived cooperation barriers are related to the following aspects of cooperation quality: perceived risk, perceived partners competencies, atmosphere/commitment, fulfillment of partners’ obligations and perceiving the partner to be trustworthy
Argument Oeconomica, 2016, Nr 1 (36), s. 165-190
Keywords: cooperation barriers; relationship quality; international cooperation